Polish Sports Club Names versus Commercialisation - Grochala, Beata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The article presents an analysis of the names of sports clubs appearing in the top-level Polish football, volleyball, basketball and hockey leagues. A total of 107 names were analysed. The research question concerned the lexical composition of the names and potential differences in naming between individual sports. The research showed a tendency for names to become longer and for sponsors’ terms to be used in their composition. The exception is the names of football clubs, which are the most established and are a market brand in their own right.